The Diagnostic Accuracy of Phalen Test and Prayer Test in Carpal Tunnel Syndrome - Suroso Agus Widodo1, Fatchur Rochman1, Ratna D. Haryadi1, Patricia Maria K1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background of Study: Carpal Tunnel Syndrome is a series of symptoms and signs because of pressure on the median nerve in a small space in the wrist called carpal tunnel. In diagnosing CTS, it is required anamnesis and thorough physical examination which includes CTS provocation test, for instance Phalen test, Prayer test, and Tinel sign. The aim of this study is to reveal the diagnostic accuracy of Phalen test and Prayer test in diagnosing CTS. Methods: The samples that fulfilled inclusion criteria were 19 subjects went through Phalen test, Prayer test, and nerve conduction study using CSI in Department of Physical Medicine and Rehabilitation Dr. Soetomo General Hospital Surabaya, Indonesia. The nerve conduction study using CSI was conducted by EMG Cadwell equipment. The data analysis was conducted by using SPSS software. Result of the Study: The sensitivity of the Phalen test and Prayer test combination in diagnosing CTS was 94.1 %. The specificity of Phalen test and Prayer test combination in diagnosing CTS was 100%. The positive predictive value was 100% while the negative predictive value was 66.7%. The result of person chisquare examination was obtained asymp. Sig value of 0.001 < ? 0.05. Conclusion: There was a correlation between the combination of Phalen test and Prayer test with CTS.